ANALISIS TINGKAT LITERASI DIGITAL GENERASI MILENIAL KABUPATEN BEKASI DALAM MENANGGULANGI PENYEBARAN HOAKS - Ratna (Jurnal Cakrawala Ilmiah, 2021)
The millennial generation was born in an era of sophisticated technology. Millennials tend to have more advanced knowledge of both technology and information. With this capability, it is supported by advances in information technology so as to provide convenience in disseminating information, thus causing difficulties in identifying whether or not the news is factual. Digital literacy is needed for millennials, especially Bekasi teenagers, considering that this generation is the most familiar with modern technology. Data were collected through a questionnaire. The results of the analysis show that the millennial generation of Bekasi city has digital literacy skills with an index score of 34.4%, which is still relatively low. The ability to understand, has the highest score with an index score of 46.8%. And the ability to collaborate has the lowest score with an index score of 32.2%